Zinc transporters maintain longevity by influencing insulin/IGF‐1 activity in Caenorhabditis elegans. Issue 9 (15th January 2020) - Novakovic, Stevan; Molesworth, Luke W.; Gourley, Taylin E.; Boag, Peter R.; Davis, Gregory M.
Abstract : Abstract : Adequate dietary intake of essential metals such as zinc is important for maintaining homeostasis. Abnormal zinc intake in Caenorhabditis elegans has been shown to increase or decrease normal lifespan by influencing the insulin/IGF‐1 pathway. Distribution of zinc is achieved by a family of highly conserved zinc transport proteins (ZIPT in C. elegans ). This study investigated the role of the zipt family of genes and showed that depletion of individual zipt genes results in a decreased lifespan. Moreover, zipt‐16 and zipt‐17 mutants synthetically interact with the insulin/IGF cofactors daf‐16 and skn‐1, and cause abnormal localisation of DAF‐16. This study suggests that the zipt family of genes are required for maintaining normal lifespan through influencing the insulin/IGF‐1 pathway.